Trajectory Control Algorithm for Open Inner Box Nine-bar Two-DOF Mechanism - Yin Mengjuan Nie Songhui Cao Zheng (Jixie chuandong)
With the extensive application of nine-bar two-DOF mechanism in light industry, packaging machinery and other equipment, it is particularly important to study the tracing algorithm to achieve the predetermined trajectory. Taking the medicine box with nine-barrel two-degree-of-freedom mechanism as the study object, it is transformed into two kinds of eight-degree single degrees of freedom mechanism, the mathematical model of motion analysis is established.Through the kinematics simulation analysis, the motion regions of two eight-bar single degree of freedom mechanism are obtained, and the trajectory and range of motion of the nine-bar two degree of freedom mechanism are obtained. Then, based on the parameterization of the mechanism and the process trajectory, the constraint conditions are established, and the tracing algorithm of the nine-bar two-degree-of-freedom mechanism to achieve the predetermined trajectory is proposed. The tracing algorithm is used to obtain a nine-bar inner box motion trajectory of the original control parameters. Finally, the tracing algorithm is improved, and the motion parameters obtained by the control parameters are used to verify the accuracy of the tracing algorithm.